Penyalahgunaan Kekebalan Diplomatik Dalam Perspektif Konvensi Wina 1961: Analisis Yuridis Terhadap Pertanggungjawaban Diplomatik Atas Tindak Pidana Di Negara Penerima - Diana Permata Hati; Thalita Olga Zhafirah; Yolanda Fitri Windia; Febrio Dosi Pratama (CV. ITTC INDONESIA, 2026)
Diplomatic immunity is a fundamental principle of international law as regulated in the Vienna Convention on Diplomatic Relations 1961. This principle is intended to ensure the smooth functioning of diplomatic missions of a sending state within the receiving state without interference. However, in practice, there have been numerous cases indicating that such immunity is misused by diplomatic officials to commit unlawful acts, including criminal offenses, without being subject to legal proceedings in the receiving state. This study focuses on two main issues: first, how diplomatic immunity is regulated under the Vienna Convention of 1961; and second, what legal consequences and forms of accountability can be imposed in cases of abuse of such immunity. The research employs a normative juridical method using statutory, conceptual, and comparative approaches to obtain a comprehensive analysis. The findings reveal that the Vienna Convention of 1961 grants extensive immunity to diplomatic agents, particularly in criminal matters, making it largely absolute in nature. Nevertheless, there remains a moral and legal obligation for diplomats to exercise such immunity responsibly. On the other hand, the receiving state has only limited mechanisms available, such as the declaration of persona non grata, which in practice is often insufficient to deliver justice, especially for victims of criminal acts. Therefore, this study recommends the need for reform in international law through the establishment of an additional protocol to the Vienna Convention, which would include exceptions to immunity in cases of serious crimes and provide a more effective and binding international dispute resolution mechanism.